The Occipital Face Area Is Causally Involved in Facial Viewpoint Perception - Kietzmann, Tim C. (J Neurosci, 2015)
Humans reliably recognize faces across a range of viewpoints, but the neural substrates supporting this ability remain unclear. Recent work suggests that neural selectivity to mirror-symmetric viewpoints of faces, found across a large network of visual areas, may constitute a key computational step in achieving full viewpoint invariance. In this study, we used repetitive transcranial magnetic stimulation (rTMS) to test the hypothesis that the occipital face area (OFA), putatively a key node in the face network, plays a causal role in face viewpoint symmetry perception. Each participant underwent both offline rTMS to the right OFA and sham stimulation, preceding blocks of behavioral trials. After each stimulation period, the participant performed one of two behavioral tasks involving presentation of faces in the peripheral visual field: (1) judging the viewpoint symmetry; or (2) judging the angular rotation. rTMS applied to the right OFA significantly impaired performance in both tasks when stimuli were presented in the contralateral, left visual field. Interestingly, however, rTMS had a differential effect on the two tasks performed ipsilaterally. Although viewpoint symmetry judgments were significantly disrupted, we observed no effect on the angle judgment task. This interaction, caused by ipsilateral rTMS, provides support for models emphasizing the role of interhemispheric crosstalk in the formation of viewpoint-invariant face perception. SIGNIFICANCE STATEMENT Faces are among the most salient objects we encounter during our everyday activities. Moreover, we are remarkably adept at identifying people at a glance, despite the diversity of viewpoints during our social encounters. Here, we investigate the cortical mechanisms underlying this ability by focusing on effects of viewpoint symmetry, i.e., the invariance of neural responses to mirror-symmetric facial viewpoints. We did this by temporarily disrupting neural processing in the occipital face area (OFA) using transcranial magnetic stimulation. Our results demonstrate that the OFA causally contributes to judgments facial viewpoints and suggest that effects of viewpoint symmetry, previously observed using fMRI, arise from an interhemispheric integration of visual information even when only one hemisphere receives direct visual stimulation.